Adherence to antihypertensive therapy in patients with uncontrolled arterial hypertension - S. Ya. Docenko (Zaporožskij Medicinskij Žurnal)
Based on a retrospective analysis, the characteristics of adherence to treatment of patients with uncontrolled arterial hypertension course were determined. Differences were found in factors groups, which were divided by patient-dependent, drug-dependent and physician-dependent adherence to antihypertensive therapy, and had significant impact on the efficiency of the control of arterial hypertension.